Taxes and financial reporting: Evidence from discretionary investment write-offs in Italy - Giampaolo Arachi; Valeria Bucci (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper provides further empirical evidence on the relationship between taxes and financial reporting by focusing on accounting decisions to write-offs equity investments. The analysis is based on panel data for Italian companies. In the period 1998-2006 the Italian corporate income tax has been reformed several times. In particular the tax deductibility of write-offs of equity investment was repealed in 2004. The paper exploits the ensuing high cross-sectional and times series variation in the marginal tax rate to identify tax effects. The econometric analysis delivers strong evidence that taxes affect the probability of write-offs. In contrast there is no evidence that taxes affect the magnitude of the write-offs. The paper also tests for the existence of a trade-off between tax minimization and non tax costs such as financial reporting costs and agency costs. Surprisingly, the evidence of such trade-off is rather weak.
Keywords: H25; H32; K34; M41; 330; corporate taxation; write-offs of equity investments; financial reporting; tax planning; Körperschaftsteuer; Steuerbegünstigung; Kapitalbeteiligung; Steuerwirkung; Bilanzpolitik; Steuerplanung; Italien